Pengembangan Model Wisata Budaya Berbasis Industri Kreatif di Ke’te Kesu, Kabupaten Toraja Utara - Darma Maraya Bangri, Abigael; Sirine, Hani (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Indonesia is a country of a thousand islands spread from Sabang to Merauke. Therefore, many foreign countries such as Britain, the Netherlands and America who wrote about Indonesia explained how beautiful and good Indonesia was. This is what other countries do not have compared to the natural beauty and cultural wealth of Indonesia, The development of tourism from year to year has a significant impact on Indonesia's economic growth, there are several important points in the development that need to be considered such as the managers / entrepreneurs of SMEs who still have their dependence on the ability to work together (synergy) with related parties, chaining creative ideas, linking to market needs (context) and creating added value, making adjustments to the environment and new technology, paying attention to the preservation of the natural and cultural environment, characterized by local cultural wisdom and nature Ke’te Kesu, has the potential of tourist attraction to visit, to buy and at the same time learn. An important contribution of cultural tourism to local communities is the sharing of good relationships with tourists, which of course means that good correlations also arise from good interaction processes. Cultural tourism has become an important role in the country's economy, where the country utilizes cultural tourism as an attraction for tourists to visit Indonesia and generate state revenue.